The Sereni Smart Bracelet: A Multimodal Sensory Wearable for Autoregulation inIndividuals with Autism Spectrum Disorder: The Sereni Smart Bracelet: A Multimodal Sensory Wearable for Autoregulation inIndividuals with Autism Spectrum Disorder - Kiehl, Isabella Tocchini (RCMOS - Revista Científica Multidisciplinar O Saber, 2025)
Background: Individuals with Autism Spectrum Disorder (ASD) frequently experiencechallenges with sensory processing, emotional regulation, communication, and focus, oftenleading to significant distress or "meltdowns." Existing market solutions for sensory supportare typically single-functional, often stigmatizing, and lack the discreet, portable designnecessary for continuous use across diverse environments. Objective: This paper introducesthe Sereni smart bracelet, a novel, multi-functional, and discreet wearable deviceconceptualized to provide personalized sensory stimuli (vibration, ASMR/binaural sounds, andlight) to support autoregulation, improve focus, and aid in crisis prevention for neurodivergentindividuals, particularly those with ASD across all support levels. Methods: We employed auser-centered design (UCD) approach informed by identified needs of autistic individuals andtheir families, as well as established principles of sensory intervention. The Sereni braceletintegrates three core sensory modalities: a central button for customizable vibrations (targetingtherapeutic frequencies between 40-120 Hz), a lateral output for user-selected ASMR andbinaural sounds, and integrated lights around the main button for visual distraction. The designprioritizes discreetness, personalization through interchangeable bands, and user comfort(hypoallergenic silicone). Results: The Sereni bracelet is positioned as an innovative "blueocean" solution, addressing a significant market gap for a comprehensive, multi-functional, andnon-stigmatizing sensory aid. Its design directly tackles the critical need for a tool that offerscontinuous support without drawing unwanted attention. The multimodal stimuli are groundedin established evidence for sensory interventions in ASD, including specific vibrationfrequencies for calming, the benefits of music therapy and light therapy. The integration of userselectable functions caters to individual sensory profiles, promoting self-management andindependence. Conclusions: The Sereni smart bracelet offers a promising, user-centeredapproach to sensory support for individuals with ASD. By empowering self-regulation throughdiscreet, customizable sensory input, it has the potential to reduce crisis severity, improve focus,and enhance overall quality of life for both autistic individuals and their families. This projectaims to bridge the gap between therapeutic needs and practical, socially acceptable wearabletechnology.